Effects of Low Carbohydrate High Fat Nigerian-Like Diet on Biochemical Indices in Rabbits - Oboh, Henrietta Ayodele; Olumese, Fidelis Ehidiamen (Pakistan Journal of Nutrition, 2010)
The effects of a low carbohydrate high fat Nigerian like diet on lipoprotein levels, serum electrolytes, liver and renal functions were investigated. The diet consist of 28% carbohydrate and 35% fat as percentage of total energy in a wholly compounded form. Twelve rabbits were randomly divided into two groups. The groups were: Group I that was fed the control diet and the second group II were fed with the low carbohydrate high fat diet. At the end of eight weeks, biochemical analyses were done on blood samples of the animals. There were significant (p<0.05) decrease in weight for the experimental animals when compared with the control group. Total protein, albumin and globulin did not change significantly (p<0.05), for the rabbits fed on the low carbohydrate high fat diet. Aspartate Transaminase (AST) and Alanine Transaminase (ALT) levels increased significantly (p<0.05) while Alkaline Phosphatase (ALP) levels decreased significantly (p<0.05). The bilirubin level for rabbits on the experimental diet did not change significantly (p<0.05). Serum electrolyte concentrations showed no significant change in sodium, potassium, chloride and bicarbonate ions when compared with control. Creatinine and urea values showed no significant (p<0.05) changes. Total Cholesterol levels were significantly (p<0.05) reduced in the experimental diet. The lipoprotein fractions showed significant increases (p<0.05) in High Density Lipoprotein (HDL) and Triacylglycerol (TAG) levels when compared with controls. Low Density Lipoprotein (LDL)-Cholesterol did not change significantly (p<0.05). The results showed that the Low Carbohydrate High Fat (LCHF) Nigerian-like diet promotes hypertriglyceridemia and weight loss. This could also increase the risk of ischemic heart disease.